A note on Aristotle’s Physics I 7, 190a31-34 - Torrente, Luca (Revista Archai, 2022)
In this note I will defend the correct understanding of a passage (Physics I 7, 190a31-34) that has been largely misunderstood by many modern commentators. The reason for the misleading translations and interpretations can be found in the presence of the problematic expression tóde ti. In what follows, I will argue that there is no mention in this text of the expression tóde ti, at least in its technical sense, that can be traced in Aristotle’s philosophy. At the beginning I will give my translation of the passage in question and some information about the context of Physics I 7. Secondly, I will give an account of the language categories of “coming to be” and I will show that Physics I 7, 190a31-34 continues in all respects this linguistic analysis. Finally, I will discuss the work of ancient commentators, which can be read according to my interpretation.